A prospective study on oral manifestations in selective IgA deficient patients in children medical center of Tehran University of Medical Sciences (2000- 2001) - Pourpak Z.; Shahrabi M.; Nikfarjam J.; Moazeni M.; Nikfarjam L.; Aghamohammadi A. (Tehran University of Medical Sciences, 2001)
"nAbstract: IgA selective deficiency is the most common immunodeficiency. The prevalence of it in different races varies from  to . Since secretary IgA has has a defensive role in the mucosal surfaces, supposing is thought that IgA deficiency will be accompanied by oral manifestations. The previous studies showed controversial results about that. The aim of this cohort study was to finding out oral manifestations in IgA- deficient individuals. As s result oral specialists can find the patients in early stages. 11 IgA- deficient patients (with IgA level < 10 mg/dl in serum) and 11 normal volunteers with the same age and sex were compared. The ages of the people were between 3 and 18 years old and 5 girls and 6 boys were in each group. Their oral examination included DMFT (Decayed, Missed and Filled Teeth), periodontal condition, Plaque accumulation and oral mucosal lesions. Saliva immunoglobulin and secretary component levels were detected by enzyme- linked immunosorbent assay (ELISA) and serum immunoglobulin levels were detected by single radial immunodiffusion (SRID) methods. All of the IgA- deficient patients had the serum IgA level < 10 mg/dl and their immunoglobulin levels were normal.  of these patients didn't have SIgA and the rest of them had a little SIgA in their saliva(<  SIgA levels in sex and age matched normal group). IgA deficient patients showed no statistical significant difference about oral manifestations in comparison with normal group. It may be related to the increase of compensatory SIgM or assistance of other non- immunological defense factors in saliva, phagocytosis and cellular immunity. Thus IgA- deficiency cannot produce any oral manifestations as a criteria to diagnose it.